The Intention to use Digital Payment in the UMKM Sector in Manado City - Jeisa Sumarauw, Zoya; Wawolumaja, Joana Elisa; Puspitasari M A Taha, Ria Kurnia; Gunadi, Willy (Riviera Publishing, 2024)
This study aims to understand and analyze how MSMEs in Manado City promote the development of digital payment usage. It employs a quantitative method, with 201 respondents particularly from the culinary sector of North Sulawesi Province, focusing on Manado City. Sampling was conducted through an online questionnaire using Google Forms distributed via social media. The research applies the Technology Acceptance Model (TAM) with modifications, incorporating perceived risk and social influence variables. Convenience sampling was utilized, and data was analyzed using SEM-PLS software. The findings demonstrate that all constructs tested—perceived ease of use, perceived usefulness, perceived risk, and social influence—can influence attitudes in encouraging MSMEs to adopt digital payment methods in their businesses. The implications of this research suggest that awareness of the importance of perceived ease of use, perceived usefulness, perceived risk, and social influence in adopting digital payments can help MSMEs increase acceptance and usage of digital payment methods in their business operations. Therefore, development and promotional strategies focusing on strengthening these factors could be key in accelerating digital payment adoption by MSMEs. Additionally, stakeholders, including the government and industry players, can utilize these findings as a basis for developing policies and support programs aimed at expanding digital payment penetration in the MSME sector.